Landing Kinematics and Isometric Hip Strength of Individuals With Chronic Ankle Instability. (August 2019) - McCann, Ryan S.; Terada, Masafumi; Kosik, Kyle B.; Gribble, Phillip A.
Background: Chronic ankle instability (CAI) is associated with hip strength deficits and altered movement in the lower extremity. However, it remains unclear how hip strength deficits contribute to lateral ankle sprain (LAS) mechanisms. We aimed to compare lower extremity landing kinematics and isometric hip strength between individuals with and without CAI and examine associations between hip kinematics and strength. Methods: Seventy-six individuals completed 5 single-leg landings, during which we collected three-dimensional ankle, knee, and hip kinematics from 200 milliseconds pre–initial contact to 50 milliseconds post–initial contact. We calculated average peak torque (Nm/kg) from 3 trials of isometric hip extension, abduction, and external rotation strength testing. One-way analyses of variance assessed group differences (CAI, LAS coper, and control) in hip strength and kinematics. Pearson product moment correlations assessed associations between hip kinematics and strength. We adjusted the kinematic group comparisons and correlation analyses for multiple comparisons using the Benjamini-Hochberg method. Results: The CAI group exhibited less hip abduction during landing than LAS copers and controls. The CAI group had lower hip external rotation strength than LAS copers ( P = .04, d = 0.62 [0.05, 1.17]) and controls ( P < .01, d = 0.87 [0.28, 1.43]). Effect sizes suggest that the CAI group had deficits in EXT compared with controls ( d = 0.63 [0.06, 1.19]). Hip strength was not associated with hip landing kinematics for any group. Conclusion: Altered landing mechanics displayed by the CAI group may promote mechanisms of LAS, but they are not associated with isometric hip strength. However, hip strength deficits may negatively impact other functional tasks, and they should still be considered during rehabilitation. Level of Evidence: Level III, case-control study.